2009
DOI: 10.1016/j.jus.2009.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound in developmental dysplasia of the hip: A screening study in Sardinian newborns

Abstract: KEYWORDSDysplasia of the hip; Ultrasound; Newborn; Screening; DDH.Abstract Introduction: Developmental dysplasia of the hip (DDH) is the most frequent inborn deformity of the locomotor apparatus. Ultrasound screening is frequently used to identify DDH in view of the brevity of the preclinical period during which diagnosis is possible. Appropriate therapeutic intervention during this period can positively affects the evolution of the disorder. Methods: An unselected population of 1158 Sardinian neonates underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The high rate of spontaneous improvement reported for DDH (>80%) has led to a considerable dilemma regarding the approach to be used for screening positive infants ( 6 ). It has been argued that ultrasound screening techniques lead to the diagnosis of a higher number of DDH cases compared with a physical examination (Ortolani and Barlow clinical tests) and that this can increase the risk of treatment being prescribed unnecessarily ( 6 ). However, an early diagnosis and treatment of DDH, made possible by ultrasound screening, can lead complete recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high rate of spontaneous improvement reported for DDH (>80%) has led to a considerable dilemma regarding the approach to be used for screening positive infants ( 6 ). It has been argued that ultrasound screening techniques lead to the diagnosis of a higher number of DDH cases compared with a physical examination (Ortolani and Barlow clinical tests) and that this can increase the risk of treatment being prescribed unnecessarily ( 6 ). However, an early diagnosis and treatment of DDH, made possible by ultrasound screening, can lead complete recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Hip ultrasound, which was described by Graf, has been used to evaluate DDH in children since the early 1980s ( 4 , 5 ). Ultrasound provides detailed visualization of the cartilaginous anatomy of the hip that is not revealed by plain X-rays and allows early detection of DDH ( 6 , 7 ). Hips with a slightly shallow acetabulum and rounded bony rim before 3 months of age are considered developmentally immature and are classified as Graf type IIa ( 5 ).…”
mentioning
confidence: 99%
“…29 Overall, 31 studies were included in the final analysis. Of these, 13 studies reported on universal ultrasound screening, [30][31][32][33][34][35][36][37][38][39][40][41][42] whereas 20 studies reported on selective ultrasound screening. 36,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] Two studies compared universal versus selective screening.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 13 studies with a total of 115,841 infants described the effect of universal ultrasound screening on the prevalence of late DDH in their population. [30][31][32][33][34][35][36][37][38][39][40][41][42] Of these studies, two were randomized controlled trials (RCTs), 33,36 two were prospective cohort studies, 38,42 six were prospective case series, 30,31,35,37,39,41 and the remaining three studies were retrospective case series. 32,40 Ten of these studies defined late DDH as those diagnosed after three months, two studies defined that as after 12 months, 33,35 and the remaining study after eight months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation